EFEKTIFITAS PENGGUNAAN DANA ALOKASI DESA DI DESA PAMMUSURENG KECAMATAN BONTO CANI KABUPATEN BONE - Ridwan Ridwan (AkMen JURNAL ILMIAH, 2011)
Utilization of Village Allocation Funds, which in essence meant as a fund for rural development that can be run solely by the villagers, so that its presence on target, then ideally it must first be compiled in a program of careful planning. Careful planning, of course, is expected to minimize the occurrence of irregularities at the time of utilization of these funds